Spuren von Ausstellungen der Kunsthalle in Sammlungen zeitgenössischer Kunst - Loock, Ulrich; Kunsthalle Bern, Bern (Bern : Kunsthalle Bern, 1994)
Brandl, Herbert ; Bustamente, Jean-Marc ; Caramelle, Ernst ; Daniëls, René ; Dorner, Helmut ; Dumas, Marlene ; Iglesias, Christina ; Klingelhöller, Harald ; Marden, Brice ; Opie, Julian ; Ruegg, Ilona ; Vercruysse, Jan
Spuren von Ausstellungen der Kunsthalle in Sammlungen zeitgenössischer Kunst, Kunsthalle Bern, 7. Mai bis 19. Juni 1994
boek